2018
DOI: 10.1007/112_2018_10
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Oxidative Stress for the Treatment of Liver Fibrosis

Abstract: Oxidative stress is a reflection of the imbalance between the production of reactive oxygen species (ROS) and the scavenging capacity of the antioxidant system. Excessive ROS, generated from various endogenous oxidative biochemical enzymes, interferes with the normal function of liver-specific cells and presumably plays a role in the pathogenesis of liver fibrosis. Once exposed to harmful stimuli, Kupffer cells (KC) are the main effectors responsible for the generation of ROS, which consequently affect hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(142 citation statements)
references
References 149 publications
0
125
0
5
Order By: Relevance
“…NOXs are a family of seven enzymes, generating O 2 ⋅− or H 2 O 2 from molecular oxygen [45]. Accumulating evidence indicates that NOX-mediated ROS production has a critical role in hepatic fibrosis [46,47], and in particular, NOX4 is involved in the severity of HCV-associated liver disease [19,36], as well as in the regulation of viral replication of different viruses [48][49][50]. Here, we found that NOX4 and NOX1 rise mirrored the trend of ROS production and that of viral replication; in fact, their expression was increased during the acute phase of infection, while it decreased late in infection, thus suggesting a critical role for NOXs also in regulating HCV replication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…NOXs are a family of seven enzymes, generating O 2 ⋅− or H 2 O 2 from molecular oxygen [45]. Accumulating evidence indicates that NOX-mediated ROS production has a critical role in hepatic fibrosis [46,47], and in particular, NOX4 is involved in the severity of HCV-associated liver disease [19,36], as well as in the regulation of viral replication of different viruses [48][49][50]. Here, we found that NOX4 and NOX1 rise mirrored the trend of ROS production and that of viral replication; in fact, their expression was increased during the acute phase of infection, while it decreased late in infection, thus suggesting a critical role for NOXs also in regulating HCV replication cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The list include vitamin E, glutathione, N-acetylcysteine, S-adenosyl-methionine, resveratrol, curcumin, herbal supplements (Sho-Saiko-to, Silymarin, Salvia Miltiorrhiza, etc. ), inhibitors of NADPH-oxidase isoforms and many others, as reviewed elsewhere (Weisenkirchen, 2016;Luangmonkong et al, 2018). Unfortunately, administration of these molecules in human patients was either ineffective or associated with very limited or transient efficacy, with few exceptions (reviewed in: Serviddio et al, 2013;Weiskirchen, 2016;Luangmonkong et al, 2018).…”
Section: Drugs To Reduce Liver Parenchymal Injurymentioning
confidence: 99%
“…), inhibitors of NADPH-oxidase isoforms and many others, as reviewed elsewhere (Weisenkirchen, 2016;Luangmonkong et al, 2018). Unfortunately, administration of these molecules in human patients was either ineffective or associated with very limited or transient efficacy, with few exceptions (reviewed in: Serviddio et al, 2013;Weiskirchen, 2016;Luangmonkong et al, 2018). For example, long-term vitamin E (96 weeks) administration has been reported to be beneficial in a multicenter, randomized, placebo-controlled study performed on non-diabetic NASH patients resulting in histological regression, reduction of liver injury and inflammation, but not fibrosis (Sanyal et al, 2010).…”
Section: Drugs To Reduce Liver Parenchymal Injurymentioning
confidence: 99%
“…Besides identifying key redox-dependent players in fibrogenesis, these approaches may also allow estimating the input of various ROS sources into the fibrogenic process by analyzing their proximity to redox switches. Altered redox signaling is considered a promising target for fibrosis treatment by targeting, e.g., mitochondrial dysfunctions, and NADPH oxidases, as detailed in [166].…”
Section: Redox Biologymentioning
confidence: 99%